Cement-Based Composites with Additive Manufacturing Technologies for Sustainable Architecture: A Review - Irem CEYLAN (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
To minimize environmental damage caused by architecture and contribute to sustainability, digital fabrication technologies, which have lower CO2 emissions and energy consumption compared to traditional production techniques, have been applied. One of the processes of digital fabrication is additive manufacturing (AM). AM technology is becoming increasingly popular due to its ability to give the designer freedom of form and its eco-friendly nature. Considering the cement-based composites applied with AM technologies, CO2 emissions can be reduced by approximately 32%. This paper aims to systematically summarize the content, improved properties, and environmental advantages of cement-based composite materials applied with AM technology and to determine the distribution of the number of studies by year. It has been observed that the studies have started to increase significantly since 2017. This indicates that cement used in architectural applications through various reinforcements and, AM technology for environmental sustainability has become more and more widespread.